A New Approach to Obtaining Nano-Sized Graphene Oxide for Biomedical Applications - Bolibok, Paulina (Materials (Basel), 2021)
Graphene oxide (GO) is one of the most exciting and widely used materials. A new method of nanographene oxide (n-GO) formation is presented. The described unique sequence of ultrasonication in dimethyl sulfoxide solution allows us to obtain different sizes of n-GO sheets by controlling the timing of the cutting and re-aggregation processes. The obtained n-GO exhibits only minor spectral changes, mainly due to the formation of S-containing surface groups; thus, it can be concluded that the material is not reduced during the process. Maintaining the initial oxygen functionalities together with the required nano-size (down to 200 nm) and high homogeneity are beneficial for extensive applications of n-GO. Moreover, we prove that the obtained material is evidently biocompatible. The calculated half-maximal effective concentration (EC50) increases by 5-fold, i.e., from 50 to 250 µg/mL, when GO is converted to n-GO. As a consequence, the new n-GO neither disturbs blood flow even in the narrowest capillaries nor triggers a toxic influence in surrounding cells. Thus, it can be a serious candidate for drugs and biomolecule carriers administered systemically.